2015
DOI: 10.1007/s00267-015-0528-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Birds Avoid Railroads as Has Been Found for Roads?

Abstract: The construction of railway lines usually has a negative effect on the natural environment: habitats are destroyed, collisions with trains cause deaths, and the noise and vibrations associated with rail traffic disturb the lives of animals. Cases are known, however, where the opposite holds true: a railway line has a positive effect on the fauna in its vicinity. In this study, we attempted to define the influence of a busy railway line on a breeding community of woodland birds. Birds were counted using the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
5

Year Published

2017
2017
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 28 publications
5
46
5
Order By: Relevance
“…There is evidence that disturbance from noise, lights, and vibrations associated with the construction and operation of the railway affect some species, and this can occur at various life cycles (van Rooyen 2009;Wiacek et al 2015). In contrast, other studies suggest that wildlife ignores or adapts to railway disturbances (Ghosh et al 2010;Mundahl et al 2013).…”
Section: Effects Of Railway Disturbance On Wildlifementioning
confidence: 99%
“…There is evidence that disturbance from noise, lights, and vibrations associated with the construction and operation of the railway affect some species, and this can occur at various life cycles (van Rooyen 2009;Wiacek et al 2015). In contrast, other studies suggest that wildlife ignores or adapts to railway disturbances (Ghosh et al 2010;Mundahl et al 2013).…”
Section: Effects Of Railway Disturbance On Wildlifementioning
confidence: 99%
“…This is the most simplistic approach, either to assess population densities (e.g., Waterman et al 2002;Li et al 2010;Wiącek et al 2015), or to calculate diversity indices of community structures (e.g., Qian et al 2009). However, it is also the most limited approach to identifying causal factors or population dynamic-related processes.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Studies to date have been carried out with simple census-based approaches, and have provided contradictory findings. For instance, whereas in the Netherlands, Waterman et al (2002) found a reduction in the density of meadow birds close to railways, Wiącek et al (2015), counting forest birds at 30, 280 and 530 m from the tracks, found higher species richness close to the railway in a Polish forest crossed by a railway. In fact, guilds like insectivorous or those ecotone-specialists were more common close to railways, and species with low-frequency calls were not averse to it (Wiącek et al 2015).…”
Section: Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that vertebrate mortality from collisions should not be a major problem because of the relatively low frequency of train circulation, although under certain conditions, it can become a relevant issue and perhaps a bigger problem than for roads running parallel to the railways (Waller and Servheen, 2005). In the case of birds, collision frequency with high speed trains is practically unknown (e.g., Loss et al, 2015), but could be high since (i) birds use areas surrounding railways and can even be attracted to them (e.g., for traditional rail lines Havlin, 1987;De la Pe-a and Llama, 1997;Mammen et al, 2002;Li et al, 2010;Wiaçek et al, 2015), (ii) slow flight birds are less able to avoid rapid trains, being then more often at risk of road or railroad-kill (Glue, 1971), and (iii) trains run at such high speeds that birds cannot evade an oncoming train .…”
Section: Introductionmentioning
confidence: 99%